Real-time implementation of self-tuning fuzzy PID controller for FOPDT system base on microcontroller STM32 - Thamma, Maitree; Homchat, Karan (2017 2nd International Conference on Control and Robotics Engineering (ICCRE), 2017)
In case of a digital communication between instruments and controller from A/D converter or of variation a model of plant. Performance of controller is degraded because of the fixed controller parameters. To solve this problem, a self-tuning fuzzy PID controller is proposed. The first order plus dead time (FOPDT) is a high dynamic system. Therefore, the controller must be intelligent. This paper presents the development and implementation of the self-tuning fuzzy PID controller for controlling the FOPDT system. The result was compared with the PID controller design using root locus technique. The water level plant used represented FOPDT system and the mathematical model of the system was approximated by using the System Identification Toolbox in MATLAB software. The control programming and the self-tuning fuzzy PID controller algorithm are used MATLAB/ Simulink. Experimental results show that, the FOPDT system has improved significantly using self-tuning fuzzy PID controller compared to the conventional PID controller.